Surface modification of ZE41A magnesium alloy using electrical discharge coating with semi sintered electrode. (10th October 2019) - Elaiyarasan, U.; Satheeshkumar, V.; Senthilkumar, C.
This present paper highlights the influence of WC/Cu composite powder metallurgy semi sintered electrode on the substrate of ZE41A magnesium alloy through electrical discharge coating (EDC). The effect of predominant process parameters such as compaction load, current and pulse on time during EDC on metal transfer rate (MTR) and surface roughness (Ra) have been studied. Experiments have been carried out through central composite design (CCD) by response surface methodology (RSM). The developed empirical model is used for analysing the machining parameters on EDC. The most significant EDC parameters were ascertained using analysis of variance (ANOVA). From the experiment results, it can be revealed that the MTR is higher at low compaction load, high current and pulse on time. Surface roughness diminished at high compaction load, low current and pulse on time. Surface morphology of coated surface has been evaluated using scanning electron microscope (SEM). Presents of elemental analysis has been carried out using energy dispersive spectroscopy (EDS).